2017
DOI: 10.1186/s12913-017-2599-z
|View full text |Cite
|
Sign up to set email alerts
|

Does one workshop on respecting cultural differences increase health professionals’ confidence to improve the care of Australian Aboriginal patients with cancer? An evaluation

Abstract: BackgroundAboriginal Australians have worse cancer survival rates than other Australians. Reasons include fear of a cancer diagnosis, reluctance to attend mainstream health services and discrimination from health professionals. Offering health professionals education in care focusing on Aboriginal patients’ needs is important. The aim of this paper was to evaluate whether participating in a workshop improved the confidence of radiation oncology health professionals in their knowledge, communication and ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 26 publications
0
58
0
1
Order By: Relevance
“…Where documents described the process of reflexivity, a variety of terms was used. The most common descriptors included ‘reflect on’ [ 21 , 22 , 23 , 27 , 30 , 31 , 32 , 33 , 36 , 56 , 64 , 66 , 67 , 68 , 73 , 80 , 90 ]; ‘examine’ [ 16 , 17 , 25 , 61 , 71 , 72 ]; ‘become aware of’ [ 17 , 18 , 36 , 63 , 68 , 75 , 88 ]; ‘explore’ [ 17 , 18 , 36 , 63 , 68 , 75 , 88 ]; ‘consider’ [ 29 , 56 , 67 , 68 ]; ‘understanding’ [ 36 , 58 , 87 ]; and ‘identify’ [ 21 , 64 , 67 , 72 , 89 ]. What is notable about these descriptors is that most—including all the most commonly used—describe a passive process of identification, observation, and awareness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Where documents described the process of reflexivity, a variety of terms was used. The most common descriptors included ‘reflect on’ [ 21 , 22 , 23 , 27 , 30 , 31 , 32 , 33 , 36 , 56 , 64 , 66 , 67 , 68 , 73 , 80 , 90 ]; ‘examine’ [ 16 , 17 , 25 , 61 , 71 , 72 ]; ‘become aware of’ [ 17 , 18 , 36 , 63 , 68 , 75 , 88 ]; ‘explore’ [ 17 , 18 , 36 , 63 , 68 , 75 , 88 ]; ‘consider’ [ 29 , 56 , 67 , 68 ]; ‘understanding’ [ 36 , 58 , 87 ]; and ‘identify’ [ 21 , 64 , 67 , 72 , 89 ]. What is notable about these descriptors is that most—including all the most commonly used—describe a passive process of identification, observation, and awareness.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five of the documents analysed described the sub-theme of held beliefs, where learners were required to identify and articulate their current knowledge, attitudes, biases, power, and privilege specifically in relation to Indigenous peoples [ 16 , 17 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 29 , 30 , 31 , 33 , 36 , 38 , 54 , 55 , 57 , 58 , 59 , 60 , 62 , 63 , 64 , 66 , 67 , 69 , 70 , 73 , 80 , 81 , 83 , 87 , 90 , 91 ]. In most of these educational interventions, learners were required to reflect on both self-identity and held beliefs, and these were conceptualised as related.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2018 systematic review of health workforce cultural competence interventions suggested health outcomes could be improved by prioritising practical skills development in training and monitoring the consistent application of these skills in healthcare encounters [ 7 ]. A later study similarly found that a single workshop could be effective in building health professionals confidence in providing culturally safe care for Indigenous Australians and that this improvement was sustained at two months [ 9 ].…”
Section: Introductionmentioning
confidence: 99%